2013
DOI: 10.1080/10408398.2011.553751
|View full text |Cite
|
Sign up to set email alerts
|

Ginger in the Prevention of Nausea and Vomiting: A Review

Abstract: Nausea and vomiting are physiological processes experienced by every human being at some stage of their life. They are complex protective mechanisms and the symptoms are influenced by the emetogenic response and stimuli. However, when these symptoms recur frequently, they can significantly reduce the quality of life and can also be detrimental to health. The existing antiemetic agents are ineffective against certain stimuli, are expensive, and possess side effects. Herbal medicines have been shown to be effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 41 publications
2
78
0
8
Order By: Relevance
“…In addition to its culinary use, ginger also possess medicinal properties, and has been used since antiquity to treat ailments like cold, headaches, nausea, stomach upset, diarrhea, digestive, gastrointestinal disturbances, rheumatic complaints, diarrhea, nausea, asthma and parasitic infections, arthritis and muscular discomfort in the various alternative and folk systems of medicine in the world [1][2][3][4][5][6][7]. Phytochemical studies have shown that the unique culinary and medicinal properties of ginger are due …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its culinary use, ginger also possess medicinal properties, and has been used since antiquity to treat ailments like cold, headaches, nausea, stomach upset, diarrhea, digestive, gastrointestinal disturbances, rheumatic complaints, diarrhea, nausea, asthma and parasitic infections, arthritis and muscular discomfort in the various alternative and folk systems of medicine in the world [1][2][3][4][5][6][7]. Phytochemical studies have shown that the unique culinary and medicinal properties of ginger are due …”
Section: Introductionmentioning
confidence: 99%
“…, β-phellandrene, curcumene, cineole, geranyl acetate, terphineol, terpenes, borneol, geraniol, limonene, β-elemene, zingiberol, linalool, α-zingiberene, β-sesquiphellandrene, β-bisabolene, zingiberenol and α-farmesene [1][2][3][4][5][6][7]. Scientific studies carried out in accordance to the principles of modern system of medicine have convincingly shown that ginger possesses numerous health benefits like antimicrobial, antiviral, gastroprotective, antidiabetic, anti-hypertensive, cardioprotective, anticancer, chemopreventive and immunomodulatory effects [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Complementary therapies such as ginger [189,190] , peppermint oil [191] , and iberogast [192] , may also have a role in the treatment of FD. Ginger enhances gastric emptying in healthy volunteers and adults with FD but had no impact on FD symptoms [193,194] .…”
Section: Targeting Electromechanical Dysfunctionmentioning
confidence: 99%
“…Usualmente, os fitoterápicos tradicionais são preparados a partir do rizoma da planta e empregados no tratamento de problemas gastrointestinais (USHA & KRISHNAPURA, 2010), agindo também como anti-inflamatório, diurético, expectorante e atuando na diminuição e controle de glicemia e colesterol (PALATTY et al, 2013). No Brasil, o conhecimento relacionado ao uso de plantas para o tratamento, prevenção de enfermidades e o seu modo de preparo é transmitido ao longo das gerações, sendo esta a principal forma de uso, mesmo com a crescente produção industrial de medicamentos e produtos fitoterápicos (OSHIRO et al, 2016).…”
unclassified